Role of laparoscopic cholecystectomy in children - Oak Sanjay; Parelkar S; Akhtar T; Pathak R; Vishwanath N (Wolters Kluwer Medknow Publications, 2005)
The present study is undertaken to establish the usefulness of laparoscopic cholecystectomy and to know its merits and demerits as compared to open cholecystectomy in children. In all, 28 patients who underwent cholecystectomy (8 open and 20 laparoscopic cholecystectomy) in B.Y.L. Nair hospital between July 1999 and March 2004 were analyzed. Calculous cholecystitis was found to be the most common indication for surgery. Operative time for laparoscopic cholecystectomy was more than that in open cholecystectomy in the early phase of laparoscopy, which got reduced as we gained experience. The requirement of parenteral antibiotics and analgesics and the duration of stay were significantly shorter with laparoscopy. The advantages for a child in laparoscopic cholecystectomy as compared to open cholecystectomy are minimal pain, avoidance of an upper abdominal incision, cosmesis and shorter duration of hospitalization with quick return to home and school. Thus, laparoscopic cholecystectomy is safe and efficacious in children.